Weak–strong uniqueness for heat conducting non-Newtonian incompressible fluids. (December 2022) - Gazca-Orozco, Pablo Alexei; Patel, Victoria
Abstract: In this work, we introduce a notion of dissipative weak solution for a system describing the evolution of a heat-conducting incompressible non-Newtonian fluid. This concept of solution is based on the balance of entropy instead of the balance of energy and has the advantage that it admits a weak–strong uniqueness principle, justifying the proposed formulation. We provide a proof of existence of solutions based on finite element approximations, thus obtaining the first convergence result of a numerical scheme for the full evolutionary system including temperature dependent coefficients and viscous dissipation terms. Then we proceed to prove the weak–strong uniqueness property of the system by means of a relative energy inequality.